Designing with the mind in mind : simple guide to understanding user interface design guidelines - Johnson, Jeff (Consultant) (Amsterdam : Morgan Kaufmann, 2014)
In this completely updated and revised edition of Designing with the Mind in Mind, Jeff Johnson provides you with just enough background in perceptual and cognitive psychology that user interface (UI) design guidelines make intuitive sense rather than being just a list or rules to follow. Early UI practitioners were trained in cognitive psychology, and developed UI design rules based on it. But as the field has evolved since the first edition of this book, designers enter the field from many disciplines. Practitioners today have enough experience in UI design that they have been exposed to design rules, but it is essential that they understand the psychology behind the rules in order to effectively apply them. In this new edition, you'll find new chapters on human choice and decision making, hand-eye coordination and attention, as well as new examples, figures, and explanations throughout. Provides an essential source for user interface design rules and how, when, and why to apply themArms designers with the science behind each design rule, allowing them to make informed decisions in projects, and to explain those decisions to others Equips readers with the knowledge to make educated tradeoffs between competing rules, project deadlines, and budget pressuresCompletely updated and revised, including additional coverage on human choice and decision making, hand-eye coordination and attention, and new mobile and touch-screen examples throughout.
Introduction -- USER-INTERFACE DESIGN RULES: WHERE DO THEY COME FROM AND HOW CAN THEY BE USED EFFECTIVELY? -- USER-INTERFACE DESIGN AND EVALUATION REQUIRES UNDERSTANDING AND EXPERIENCE -- COMPARING USER-INTERFACE DESIGN GUIDELINES -- WHERE DO DESIGN GUIDELINES COME FROM? -- INTENDED AUDIENCE OF THIS BOOK -- Chapter 1 -- Our Perception is Biased -- PERCEPTION BIASED BY CURRENT CONTEXT -- PERCEPTION BIASED BY GOALS -- TAKING BIASED PERCEPTION INTO ACCOUNT WHEN DESIGNING -- Chapter 2 -- Our Vision is Optimized to See Structure -- GESTALT PRINCIPLE: PROXIMITY -- GESTALT PRINCIPLE: SIMILARITY -- GESTALT PRINCIPLE: CONTINUITY -- GESTALT PRINCIPLE: CLOSURE -- GESTALT PRINCIPLE: SYMMETRY -- GESTALT PRINCIPLE: FIGURE/GROUND -- GESTALT PRINCIPLE: COMMON FATE -- GESTALT PRINCIPLES: COMBINED -- Chapter 3 -- We Seek and Use Visual Structure -- STRUCTURE ENHANCES PEOPLE'S ABILITY TO SCAN LONG NUMBERS -- DATA-SPECIFIC CONTROLS PROVIDE EVEN MORE STRUCTURE -- VISUAL HIERARCHY LETS PEOPLE FOCUS ON THE RELEVANT INFORMATION -- Chapter 4 -- Our Color Vision is Limited -- HOW COLOR VISION WORKS -- VISION IS OPTIMIZED FOR CONTRAST, NOT BRIGHTNESS -- THE ABILITY TO DISCRIMINATE COLORS DEPENDS ON HOW COLORS ARE PRESENTED -- COLOR-BLINDNESS -- EXTERNAL FACTORS THAT INFLUENCE THE ABILITY TO DISTINGUISH COLORS -- GUIDELINES FOR USING COLOR -- Chapter 5 -- Our Peripheral Vision is Poor -- RESOLUTION OF THE FOVEA COMPARED TO THE PERIPHERY -- IS THE VISUAL PERIPHERY GOOD FOR ANYTHING? -- EXAMPLES FROM COMPUTER USER INTERFACES -- COMMON METHODS OF MAKING MESSAGES VISIBLE -- HEAVY ARTILLERY FOR MAKING USERS NOTICE MESSAGES -- VISUAL SEARCH IS LINEAR UNLESS TARGETS "POP" IN THE PERIPHERY -- Chapter 6 -- Reading is Unnatural -- WE'RE WIRED FOR LANGUAGE, BUT NOT FOR READING -- IS READING FEATURE-DRIVEN OR CONTEXT-DRIVEN? -- SKILLED AND UNSKILLED READING USE DIFFERENT PARTS OF THE BRAIN -- POOR INFORMATION DESIGN CAN DISRUPT READING -- MUCH OF THE READING REQUIRED BY SOFTWARE IS UNNECESSARY -- TEST ON REAL USERS -- Chapter 7 -- Our Attention is Limited; Our Memory is Imperfect -- SHORT- VERSUS LONG-TERM MEMORY -- A MODERN VIEW OF MEMORY -- CHARACTERISTICS OF ATTENTION AND WORKING MEMORY -- IMPLICATIONS OF WORKING MEMORY CHARACTERISTICS FOR USER-INTERFACE DESIGN -- CHARACTERISTICS OF LONG-TERM MEMORY -- IMPLICATIONS OF LONG-TERM MEMORY CHARACTERISTICS FOR USER-INTERFACE DESIGN -- Chapter 8 -- Limits on Attention Shape Our Thought and Action -- WE FOCUS ON OUR GOALS AND PAY LITTLE ATTENTION TO OUR TOOLS -- WE NOTICE THINGS MORE WHEN THEY ARE RELATED TO OUR GOALS -- WE USE EXTERNAL AIDS TO KEEP TRACK OF WHAT WE ARE DOING -- WE FOLLOW THE INFORMATION "SCENT" TOWARD OUR GOAL -- WE PREFER FAMILIAR PATHS -- OUR THOUGHT CYCLE: GOAL, EXECUTE, EVALUATE -- AFTER WE ACHIEVE A TASK'S PRIMARY GOAL, WE OFTEN FORGET CLEANUP STEPS -- Chapter 9 -- Recognition is Easy; Recall is Hard -- RECOGNITION IS EASY -- RECALL IS HARD -- RECOGNITION VERSUS RECALL: IMPLICATIONS FOR USER-INTERFACE DESIGN -- Chapter 10 -- Learning from Experience and Performing Learned Actions are Easy; Novel Actions, Problem Solving, and Calculation are Hard -- WE HAVE THREE BRAINS -- WE HAVE TWO MINDS -- LEARNING FROM EXPERIENCE IS (USUALLY) EASY -- PERFORMING LEARNED ACTIONS IS EASY -- PERFORMING NOVEL ACTIONS IS HARD -- PROBLEM SOLVING AND CALCULATION ARE HARD -- IMPLICATIONS FOR USER-INTERFACE DESIGN -- ANSWERS TO PUZZLES -- Chapter 11 -- Many Factors Affect Learning -- WE LEARN FASTER WHEN PRACTICE IS FREQUENT, REGULAR, AND PRECISE -- WE LEARN FASTER WHEN OPERATION IS TASK FOCUSED, SIMPLE, AND CONSISTENT -- WE LEARN FASTER WHEN VOCABULARY IS TASK FOCUSED, FAMILIAR, AND CONSISTENT -- WHEN RISK IS LOW, WE EXPLORE MORE AND LEARN MORE -- Chapter 12 -- Human Decision Making is Rarely Rational -- PEOPLE ARE OFTEN IRRATIONAL -- LOSSES MEAN MORE TO US THAN GAINS -- WE ARE BIASED BY HOW CHOICES ARE WORDED -- WE ARE BIASED BY OUR VIVID IMAGINATIONS AND MEMORIES -- EXPLOITING STRENGTHS AND WEAKNESSES OF HUMAN COGNITION -- Chapter 13 -- Our Hand-Eye Coordination Follows Laws -- FITTS' LAW: POINTING AT DISPLAYED TARGETS -- STEERING LAW: MOVING POINTERS ALONG CONSTRAINED PATHS -- Chapter 14 -- We Have Time Requirements -- RESPONSIVENESS DEFINED -- THE MANY TIME CONSTANTS OF THE HUMAN BRAIN -- ENGINEERING APPROXIMATIONS OF TIME CONSTANTS: ORDERS OF MAGNITUDE -- DESIGNING TO MEET REAL-TIME HUMAN INTERACTION DEADLINES -- ADDITIONAL GUIDELINES FOR ACHIEVING RESPONSIVE INTERACTIVE SYSTEMS -- ACHIEVING RESPONSIVENESS IS IMPORTANT -- EPILOGUE.
Includes bibliographical references and index.
Print version record.
Keywords: Graphical user interfaces (Computer systems); COMPUTERS -- User Interfaces; Graphical user interfaces (Computer systems); Computer Graphics; User-Computer Interface; Electronic books